LAHAN POTENSIAL PERMUKIMAN DI KOTA SEMARANG - Hala Haidir; Iwan Rudiarto (TATALOKA, 2019)
The increase and spread of population between regions always have an impact on settlements, whereby settlements require a land while land in a city has many activities, and it is limited. This limited potential settlement lands greatly influence the direction of the population in finding a place to settle. This study aims to study on potential settlement land in Semarang City. The methods used are quantitative descriptive and spatial descriptive that consist of settlement land suitability analysis (overlaying and weighting), potential settlement land analysis (buffering, overlaying and weighting), population growth analysis, settlement carrying capacity analysis, and distribution of population analysis. The results showed that the most available sub-district of potential settlement land is Mijen Subdistrict, and the total potential land area in Semarang City is 7,006 Ha. The results of the potential land are the destination for the direction of population distribution for sub-districts that do not have potential settlement land. Among others, are spread in West Semarang District, Tugu District, Ngaliyan District, Mijen District, Gunung Pati District, Tembalang District, and Pedurungan District.